KEMAMPUAN REPRESENTASI DALAM MEMECAHKAN MASALAH MATEMATIKA BERDASARKAN GAYA BELAJAR - Yarmayani, Ayu (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
Solving problems requires the ability to recall the information needed and represented both visually and verbally. This information is obtained, managed and recalled through a system called learning style. This research was conducted at Asy-Syifa Al-Inayah Middle School, Jambi City, with the aim of obtaining a description of student representation in solving mathematical problems. Subjects in this study were selected using purposive sampling based on visual, auditory and kinesthetic learning styles. It is hoped that this research will provide benefits in improving mathematics learning. The results of the research show that the representation of auditory students and visual students in solving mathematical problems each fulfills three indicators, while kinesthetic students only fulfill two indicators of mathematical representation. In presenting information, visual and auditory subjects each tend to present it in the form of images (geometry or number patterns) and create situations based on the problem given. Meanwhile, kinesthetic subjects tend to only create images to clarify problems and facilitate their resolution. In solving problems, both visual and auditory subjects are able to solve problems by making patterns based on the problem given and making conclusions from a pattern. It's just that auditory subjects can shorten problem solving steps by using mathematical expressions. Meanwhile, kinesthetic subjects experience problems in solving combinatorics problems, where they are unable to present images or patterns that can help solve the problem.